Axiology in Latvia`s Insolvency policy - Savickis, Valdis (European Journal of Sustainable Development, 2020)
The closing period for the validity of the policy planning documents in the sphere of insolvency proceedings in the Republic of Latvia is approaching (the Insolvency Policy Development Guidelines 2016-2020, as well as their implementation plan). Given the extensive work done by the state on reforming and reorganizing the insolvency and regulatory framework, the author focuses on the axiological aspect of the insolvency policy. Parallel to the modernization of the insolvency process, because of which the role of the state in the control and supervision of the insolvency sector has significantly increased and considering the correlation between the speed and efficiency of insolvency process, there will be conducted value-oriented study on the insolvency sector. The aim of the paper is to carry out research and analysis of insolvency policy through the prism of axiology. The study uses analytical, descriptive, and deduction/induction methods, evaluating the various policy planning documents that make up insolvency policy, paying attention to the specifics of the insolvency process of legal entities. Keywords: Insolvency policy, axiology, value, business environment